TIMI risk score for secondary prevention of recurrent cardiovascular events in a real-world cohort of post-non-ST-elevation myocardial infarction patients. Issue 1125 (23rd May 2019) - Huang, Duo; Cheng, Yang Yang; Wong, Yiu Tung; Yung, See Yue; Chan, Ki Wan; Lam, Cheung Chi; Hai, JoJo; Lau, Chu Pak; Wong, Ka Lam; Feng, Ying Qing; Tan, Ning; Chen, Ji Yan; et al.
Abstract: Background: Patients who survive non-ST-elevation myocardial infarction (NSTEMI) are at heightened risk of recurrent cardiovascular events. Data on long-term secondary atherothrombotic risk stratification are limited. Objectives: To stratify post-NSTEMI patients for risk of recurrent cardiovascular events to maximise benefit from aggressive secondary prevention strategies using the TIMI Risk Score for Secondary Prevention (TRS 2°P) score in a real-world cohort of NSTEMI patients. Methods and results: This was a single-centre observational study of 891 post-NSTEMI patients (73.7 ± 12.7 years; male: 54.2%). The TRS 2°P is a nine-point risk stratification tool to predict cardiovascular events in patients with established cardiovascular disease. The primary outcome was a composite endpoint of cardiovascular death, non-fatal MI and non-fatal ischaemic stroke. After a median follow-up of 31 months (IQR: 11.4 – 60.2), 281 patients (31.5%) had developed a primary outcome (13.3%/year) including 196 cardiovascular deaths, 94 non-fatal MIs and 22 non-fatal strokes. The TRS 2°P score was strongly associated with the primary outcome. The annual incidence of primary composite endpoint for patients with TRS 2°P score =0 was 1.6%, and increased progressively to 47.4% for those with a TRS 2°P score ≥6 (HR: 20.18, 95% CI: 4.85 to 84.05, p<0.001). Similar associations were also observed between the TRS 2°P score and cardiovascular death and MI (fatal and non-fatal), but not non-fatal ischaemic stroke. Conclusion: The TRS 2°P score stratified post-NSTEMI patients for risk of future cardiovascular events and potentially help guide the selection of more aggressive secondary prevention therapy.